Mergers and acquisitions in the automotive supplier industry : the acquisition of TRW by ZF Friedrichshafen - Häusl, Markus (2016)
A lack of technological foresight and changing economic conditions have led to an increasing consolidation in the automotive supplier industry. In 2014, with the takeover of TRW Automotive Holding by ZF Friedrichshafen AG we have seen the largest transaction ever so far in this sector. This paper aims to analyze the transaction and comments on whether the transaction is reasonable from both an economic and strategic point of view. Hereby, both companies are valued on a standalone basis using different valuation methodologies and thereafter potential synergies are addressed and evaluated. As the transaction has been successfully completed in the meanwhile on May 15, 2015, a comparison with the real deal terms could be done. Putting the transaction value of EUR 77.66 (USD 105.60) for each TRW share in context with the identified synergy potential the acquisition is expected to bring along, leads to the conclusion that the deal not only creates value to ZF, but also perfectly makes sense for ZF from a strategic perspective.